The Relationship of Characteristics Individual and Personal Hygiene with Symptoms of Dermatitis Contact on Scavengers - Rosdiana, Rosdiana; Ekowati Januariana, Neni; Sarah, Fatia (Jurnal Perilaku Kesehatan Terpadu, 2023)
Skin disease is a condition that affects the body's surface and has a number of causes. The most prevalent infectious illnesses that afflict people of all ages are skin conditions. The majority of skin infection treatments take a while to start working. The goal of this study was to ascertain how scavengers at the Medan City Waste Landfill's personal hygiene habits and contact dermatitis symptoms related to one another. Approach: This study uses a cross-sectional analytic survey design as its methodology. The population of this study consisted of 72 respondents who served as research samples. They were all scavengers in Environment VII of the Waterfall Village. The chi-square statistical test was utilized in the univariate and bivariate analyses. The Findings: Scavengers' symptoms of contact dermatitis were related to age (p = 0.019), education (p = 0.021), length of labor (p = 0.007), and personal hygiene (p = 0.000). The study's findings suggest that scavengers in the Medan City Waste Landfill may have contact dermatitis symptoms in relation to their age, education, length of employment, and personal hygiene. It is planned that TPA Falls would offer health education about skin conditions, including dermatitis, so that scavengers may avoid contracting these illnesses by practicing good personal hygiene after work, including as cleaning their hands, feet, and taking a shower.